Narrative Subversion: Representations of “Marginalized Culture” in Narrative Fiction - Ibrahim, Alaa (El Omda in Linguistics and Discourse Analysis, 2019)
<section class="text-token-text-primary w-full focus:outline-none [--shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(--shadow-height) has-data-writing-block:pt-(--shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto scroll-mt-(--header-height)" dir="auto" data-turn-id="656c2a8c-7bfc-445f-8388-7b3ac96bb3c1" data-testid="conversation-turn-89" data-scroll-anchor="false" data-turn="user"> <section class="text-token-text-primary w-full focus:outline-none [--shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(--shadow-height) has-data-writing-block:pt-(--shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto scroll-mt-[calc(var(--header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-WEB:32c27e8d-0406-4310-8c57-7cfb6e3aa634-44" data-testid="conversation-turn-90" data-scroll-anchor="true" data-turn="assistant"><div class="text-base my-auto mx-auto pb-10 [--thread-content-margin:var(--thread-content-margin-xs,calc(var(--spacing)*4))] @w-sm/main:[--thread-content-margin:var(--thread-content-margin-sm,calc(var(--spacing)*6))] @w-lg/main:[--thread-content-margin:var(--thread-content-margin-lg,calc(var(--spacing)*16))] px-(--thread-content-margin)"><div class="[--thread-content-max-width:40rem] @w-lg/main:[--thread-content-max-width:48rem] mx-auto max-w-(--thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="da8ceb3d-31c5-48eb-b0db-dad6221b4398" data-message-model-slug="gpt-5-mini" data-turn-start-message="true"> The narrative writings concerned with representing daily life among a broad human sector—representing the “cultural margin” in contrast to the “cultural center,” inherently elitist—have undergone numerous readings and revisions, approached in modern times from formal and functional perspectives. However, the epistemological challenges posed by this type of narrative continue to emerge, and the questions generated by sustained interaction with it are virtually inexhaustible. The present study seeks to address some of these imposed challenges and respond to questions arising within the field of cultural textual criticism, treating the text as a “cultural event” rather than merely an aesthetic literary object. This perspective moves beyond formalist criticism and its methods preoccupied with constructing universal models and rigid structures, which assert dominant authority through the presence of the cultural author—“a cultural product shaped primarily by culture, whose discourse may convey meanings not consciously intended by the author, nor perceived by the cultural audience, yet these implicit meanings provide indications that may contradict the apparent discourse.” The study starts from the premise that cultural dimensions influence us and our discourses, affecting the effectiveness of the communicative process. In this interaction, the systemic meaning interacts with its aesthetic counterpart—both explicit and implicit—because textual structure is formed through a reciprocal movement between the internal textual space and external components. Consequently, reading the elements forming textual architecture leads to an interpretation of meaning that is open to discussion, induction, analysis, and comprehension in light of reality and its circumstances. Based on this conception of the cultural systemic function of the text, this study focuses on tracing the narrative representation of cultural systems—both manifest and latent—embedded within the structure of a novel rich in popular culture manifestations: the novel Laḥs al-‘Atab by the Egyptian author Khairy Shalaby.